The Israeli-Iranian War and its environmental repercussions: A study on the targeting of nuclear facilities - Mehenni, Kamal; Ahcene, Rafa Debbah; Boulekouane, Ismail; Goug, Soufiane (The International tax journal, 2025)
On June 13, 2025, the Zionist entity launched sudden and unannounced attacks on the state of Iran through a direct military operation targeting vital Iranian facilities, namely missile strikes on nuclear sites and military zones. The consequences extended beyond this, including the killing of unarmed civilians. On another level, this blatant aggression by the ruthless Zionist occupier is expected to have severe repercussions on the region, particularly with regard to radioactive pollution, which will inevitably have a negative impact on environmental degradation, exacerbate climate change, and intensify problems such as land degradation and the loss of biodiversity. In addition, the dispersed gases are likely to have a harmful effect on the ozone layer. The international response has included widespread condemnation of this inhumane act of aggression. In retaliation, Iran responded in kind by launching missile strikes deep into Israeli territory, targeting nuclear facilities—an escalation with potentially catastrophic consequences for both the region and the international community. Through this research paper, we aim to examine nuclear reactors and their link to radioactive pollution, as well as the environmental impact of targeting nuclear facilities.